THE REASONS FOR THE DEVELOPMENT OF THE REVOLUTION ON GRANITE – “A HARDY PLANT”, WHICH WAS GRADUALLY GROWING IN THE SOIL, “DRIED BY BURNING RAYS” OF A SOVIET SYSTEM FROM “THE SEEDS” OF NATIONAL AWAKENING” - Гурський, Ігор (Modern engineering and innovative technologies, 2022)
The article deals with the reasons for the development of the Revolution on granite taking place on October 2–17, 1990. The relevance of scientific research is objectified by the research focus on a detailed analysis of the historical background of Ukrai